Study Protocol for a Global Survey: Awareness and Preparedness of Hospital Staff Against Coronavirus Disease (COVID-19) Outbreak - Qarawi, Ahmad Taysir Atieh; Ng, Sze Jia; Gad, Abdelrahman; Luu, Mai Ngoc; AL-Ahdal, Tareq Mohammed Ali; Sharma, Akash; Huan, Vuong Thanh; Vuong, Nguyen Lam; Tawfik, Gehad Mohamed; Hashan, Mohammad Rashidul; Dumre, Shyam Prakash; Ghozy, Sherief; et al. (Frontiers in Public Health, 2021)
Background: The outbreak of Coronavirus disease (COVID-19) caused by a novel coronavirus (named SARS-CoV-2) has gained attention globally and has been recognized as a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (WHO) due to the rapidly increasing number of deaths and confirmed cases. Health care workers (HCWs) are vulnerable to this crisis as they are the first frontline to receive and manage COVID-19 patients. In this multicenter multinational survey, we aim to assess the level of awareness and preparedness of hospital staff regarding COVID-19 all over the world. Methods: From February to March 2020, the web-based or paper-based survey to gather information about the hospital staff's awareness and preparedness in the participants' countries will be carried out using a structured questionnaire based on the United States Centers for Disease Control and Prevention (CDC) checklist and delivered to participants by the local collaborators for each hospital. As of March 2020, we recruited 374 hospitals from 58 countries that could adhere to this protocol as approved by their Institutional Review Boards (IRB) or Ethics Committees (EC). Discussion: The awareness and preparedness of HCWs against COVID-19 are of utmost importance not only to protect themselves from infection, but also to control the virus transmission in healthcare facilities and to manage the disease, especially in the context of manpower lacking and hospital overload during the pandemic. The results of this survey can be used to inform hospitals about the awareness and preparedness of their health staff regarding COVID-19, so appropriate policies and practice guidelines can be implemented to improve their capabilities of facing this crisis and other future pandemic-prone diseases.